Agricultural new-quality productive forces empowering rural common prosperity: examining the mediating mechanism of village digitalization - Peng, Yan; Tan, Chang; Huang, Dahu; Li, Pingheng (Frontiers in Sustainable Food Systems, 2025)
As a crucial engine driving the modernization of agriculture and rural areas, new-quality productive forces in agriculture reshape rural development patterns through technical innovation and organizational transformation, playing a key role in achieving common rural prosperity. Based on panel data from 30 provinces in China from 2012 to 2022, this study systematically examined the direct impact effects and mechanisms of new agricultural productive forces on rural common prosperity, with a focus on revealing the mediating transmission mechanism of rural digitalization. Heterogeneity tests were conducted from the perspective of regional differences and functional zoning. The findings indicate that new agricultural productive forces have significant positive promotional effects on common rural prosperity and that rural digitalization plays a partial mediating role between them, accounting for 25.6% of the mediating contribution. Heterogeneity analysis shows that the driving effect of agricultural new-quality productive forces presents a gradient decrease characteristic of “western > central > eastern” and is significant in grain-producing areas (effect value 0.446), while it is not significant in non-grain-producing areas. These conclusions provide theoretical support for optimizing the layout of agricultural new-quality productive forces and implementing differentiated digital village strategies, offering important policy implications for comprehensively promoting rural revitalization and common prosperity, both of which contribute to the sustainable development of society.